Plasma levels of miR-30d-5p are decreased in regularly exercising postmenopausal women. Issue 3 (March 2020) - Kranjc, Tilen; Milojević, Marko; Kocjan, Tomaž; Jensterle, Mojca; Marc, Janja; Ostanek, Barbara
Abstract: Objective: Plasma/serum microRNAs (miRNAs) are proposed to have a role in the development of osteoporosis, and their levels can be affected by physical activity. Therefore, the aim of this study was to analyze differences in plasma miRNAs levels in postmenopausal women and to simultaneously find novel extracellular miRNAs that are associated with variations in physical activities. Methods: We measured hsa-miR-148a-3p, hsa-miR-125b, hsa-miR-21-5p, hsa-miR-93-5p, and hsa-miR-30d-5p in a cohort of 149 postmenopausal women divided into subgroups based on the amount of physical activity by using quantitative polymerase chain reaction (qPCR). Further, the correlation of plasma microRNAs with sit-to-stand performance was examined. DIANA web server was used to find which Kyoto Encyclopedia of Genes and Genomes pathways ( P  < 0.05) were regulated by miRNAs associated with physical activity and sit-to-stand performance. Results: Plasma levels of hsa-miR-30d-5p were significantly ( P  = 0.015) lower in participants with higher physical activity, and a borderline trend for hsa-miR-21-5p ( P  = 0.06) was noticed. Higher plasma levels of hsa-miR-21-5p ( P  = 0.01) and hsa-miR-93-5p ( P  = 0.04) were observed in the group with reduced sit-to-stand performance. The two miRNAs seem to primarily regulate fatty acid metabolism-related processes. Conclusions: Our results suggest that levels of selected cell-free miRNAs in postmenopausal women are associated with different physical activity regimes.